Studying the Effect of Organoleptic and Physical Properties on Milk Productivity in Cows - Khamidova, R.N.; Khujamov, J.N.; Avalbekova, S.O. (American Journal of Biomedicine and Pharmacy, 2025)
This article explores the factors affecting milk productivity in cows. Research results demonstrate that organoleptic and physical properties have a considerable impact. Information is provided regarding milk quality.